Governing in the face of a global crisis: When do voters punish and reward incumbent governments? - Raymond M. Duch; Peter Loewen; Thomas S. Robinson; Alexei Zakharov (Proceedings of the National Academy of Sciences, 2025)
The recent COVID-19 pandemic offers a rare opportunity to understand how citizens attribute responsibility for governments’ responses to unanticipated negative—and in this case, systemic—exogenous shocks. Classical accounts of responsibility are complicated when crises are pervasive, involve multiple valence dimensions, and where individuals can make relative assessments of performance. We fielded a conjoint experiment in 16 countries with 22,147 respondents. In this experiment, subjects made re-election decisions regarding 178,184 randomly assigned incumbent profiles. We find that incumbents’ performance along both health and economic dimensions drives these hypothetical reelection decisions. Using machine learning techniques, we find only muted heterogeneity in the magnitude and distribution of these treatment effects. This result suggests that these widely reported performance signals have consistent political effects across countries. In a complementary analysis, we also find that subjects’ intentions to vote for incumbent governments are positively correlated with subjective and relative evaluations of the government’s pandemic performance, along both health and economic dimensions. These results provide consistent evidence that evaluations of pandemic performance matter politically.